2016
DOI: 10.1210/er.2016-1047
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ovarian Insufficiency: New Perspectives on Genetic Cause and Phenotypic Spectrum

Abstract: Premature ovarian insufficiency (POI) is one form of female infertility, defined by loss of ovarian activity before the age of 40 and characterized by amenorrhea (primary or secondary) with raised gonadotropins and low estradiol. POI affects up to one in 100 females, including one in 1000 before the age of 30. Substantial evidence suggests a genetic basis for POI; however, the majority of cases remain unexplained, indicating that genes likely to be associated with this condition are yet to be discovered. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
182
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(185 citation statements)
references
References 236 publications
2
182
0
1
Order By: Relevance
“…POI is a dysfunction of the ovary caused by heterogeneous factors (viral infections, autoimmune disorders, genetic disorders, iatrogenic causes), among which the genetic component plays a substantial role, as the synergistic action of different mutations may underlie the development of this phenotype (Rossetti, Ferrari, Bonomi, & Persani, 2017; Tucker, Grover, Bachelot, Touraine, & Sinclair, 2016). Relatively a few genes are considered involved in the development of syndromic and nonsyndromic POI (Cox & Liu, 2014; Fortuno & Labarta, 2014).…”
Section: Gdf9 and Bmp15 In Dizygotic Twinning Poi And Pcosmentioning
confidence: 99%
“…POI is a dysfunction of the ovary caused by heterogeneous factors (viral infections, autoimmune disorders, genetic disorders, iatrogenic causes), among which the genetic component plays a substantial role, as the synergistic action of different mutations may underlie the development of this phenotype (Rossetti, Ferrari, Bonomi, & Persani, 2017; Tucker, Grover, Bachelot, Touraine, & Sinclair, 2016). Relatively a few genes are considered involved in the development of syndromic and nonsyndromic POI (Cox & Liu, 2014; Fortuno & Labarta, 2014).…”
Section: Gdf9 and Bmp15 In Dizygotic Twinning Poi And Pcosmentioning
confidence: 99%
“…Aneuploidies comprise 13% of all POI cases, whereas X‐chromosome structural abnormalities, for example, Xq isochromosome, translocations or deletion, are seen less frequently. Another sex chromosomal abnormality leading to streak ovaries is 46,XY gonadal dysgenesis …”
Section: Non‐iatrogenic Causes Of Poimentioning
confidence: 99%
“…Mutations in FMR1 , NR5A1 , NOBOX , FIGLA , FOXL2 , SOHLH1/2 , BMP15 , GDF9 , INHA , and ESR1 , in addition to FSHR and LHR, have been implicated in congenital defects of folliculogenesis and ovarian development and function [Tucker et al, 2016]. Previous work from our group has shown that mutations in NANOS3 , which were also identified by Sanger sequencing, are implicated in POF etiology through a mechanism involving increased apoptosis of the primordial germ cells during embryonic cell migration [Santos et al, 2014].…”
mentioning
confidence: 96%
“…Although a number of chromosome abnormalities have been associated with HH, a monogenic cause is still unknown. Primary ovarian failure (POF), also known as premature ovarian insufficiency, is the loss of ovarian function before the age of 40 years and is characterized by amenorrhea, hypoestrogenism, and elevated gonadotropin levels (follicle-stimulating hormone [FSH] >40 U/L), resulting in loss of fertility [Shelling, 2010;Tucker et al, 2016]. Chemotherapy or radiotherapy, autoimmune disease, X chromosome abnormalities, and genetic conditions have been described as causes of POF; however, approximately 65% of POF casKeywords FSHR · Homozygous missense · Hypergonadotropic hypogonadism · Infertility · Whole-exome sequencing Abstract Hypergonadotropic hypogonadism (HH) is defined by increased gonadotropin levels in men and women.…”
mentioning
confidence: 99%